Efficient and secure message authentication scheme for VANET - Li-bing WU; Yong XIE; Yu-bo ZHANG (Tongxin xuebao, 2016)
A new efficient identity-based message authentication scheme for VANET was proposed. The proposed scheme decreased the complexity of cryptographic operations on signature by using elliptic curve cryptosystem (ECC) to construct authentication protocol without bilinear pairing and provided the function of conditional privacy-preserving. Security analysis demonstrated that the proposed scheme satisfies all security and privacy requirements for VANET. Per-formance analysis show that compared with the most recent proposed schemes the proposed scheme decreases the com-putation cost and communication cost.